Articular cartilage zonal differentiation via 3D Second-Harmonic Generation imaging microscopy. (24th February 2015) - Chaudhary, Rajeev; Campbell, Kirby R.; Tilbury, Karissa B.; Vanderby, Ray; Block, Walter F.; Kijowski, Richard; Campagnola, Paul J.
Abstract: Purpose : The collagen structure throughout the patella has not been thoroughly investigated by 3D imaging, where the majority of the existing data come from histological cross sections. It is important to have a better understanding of the architecture in normal tissues, where this could then be applied to imaging of diseased states. Methods : To address this shortcoming, we investigated the combined use of collagen-specific Second-Harmonic Generation (SHG) imaging and measurement of bulk optical properties to characterize collagen fiber orientations of the histologically defined zones of bovine articular cartilage. Forward and backward SHG intensities of sections from superficial, middle and deep zones were collected as a function of depth and analyzed by Monte Carlo simulations to extract the SHG creation direction, which is related to the fibrillar assembly. Results : Our results revealed differences in SHG forward–backward response between the three zones, where these are consistent with a previously developed model of SHG emission. Some of the findings are consistent with that from other modalities; however, SHG analysis showed the middle zone had the most organized fibril assembly. While not distinct, we also report bulk optical property values for these different zones within the patella. Conclusions : Collectively, these results provide quantitative measurements of structural changes at both the fiber and fibril assembly of the different cartilage zones and reveals structural information not possible by other microscope modalities. This can provide quantitative insight to the collagen fiber network in normal cartilage, which may ultimately be developed as a biomarker for osteoarthritis.